Penerapan HACCP Bubur Bayi Beras Merah Terhadap Penerimaan dan Lama Waktu Simpan - Riska Listyanti; Narto Narto; Lilik Hendrarini (Sanitasi: Jurnal Kesehatan Lingkungan, 2017)
In general, this study was aimed to implementing HACCP for brown rice porridge that to be consumed by 6-10 month aged infant; and specifically was to define the differences of shelf life of the porridge, between those that applied HACCP (variation 1) with the porridge that has HACCP but without controlling the CCP related to: preparation of materials (variation 2), utensils sanitation (variation 3), handlers (variation 4), processing method (variation 5), storage (variation 6) and serving (variations 7); and to determine the differences in acceptance of brown rice porridge of variation 1 and organic porridge as positive control. These aims were backgrounded because in the making process of brown rice porridge by baby's mother, as well as of the organic porridge, the selection of materials, utensils sanitation, handling and processing methods were inadequate. The data collection used was observation, and the observed porridge were made by the researcher herself. The results of analysis show the homogenization baby who accepted thered rice porridge was 73,25 %, meanwhile those who accepted the commercial organic porridge was 46,5 %. Those acceptance were significantly different (p-value: 0,022). It is also known that the shelf-life of variation 1 of the brown rice porridge was more than 12 hours; variation 2, 12 hours (p-value: 1,00); variation 3, 12 hours (p-value: 0,831); variation 4, 11 hours (p-value: 0,862); variation 5, 11 hours (p-value: 0,478); variation 6, 8 hours (p-value: 0,155); and variations 7, 11 hours (p-value: 0,473). Therefore it can be concluded that the shelf-life of variation 2, 3, 4, 5, dan 6 of the porridge is not different with that of variation 1.